International capital mobility and the CARICOM countries. - BENNETT, Karl M. (1996)
Examines the potential for CARICOM Member States to attract private capital inflows. Notes that an ability to attract such inflows would be of particular significance to Barbados, Jamaica, Guyana and Trinidad and Tobago.